Scaffoldings used during the renovation of the Metropolitan Cathedral of St. John the Baptist and St. John the Evangelist in Lublin = Rusztowania wykorzystywane podczas renowacji Archikatedry Św. Jana Chrzciciela i Św. Jana Ewangelisty w Lublinie - Pieńko, Michał; Robak, Aleksander; Błazik-Borowa, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article describes three cases of scaffolding use as a structure for carrying out a renovation work at the Cathedral in Lublin. In order to achieve optimum access to the object, one used modular scaffolding. This type of scaffold is able to expand in any direction. In addition to the typical use, the scaffold was used as temporary roofing which allowed conducting the work during the winter. Monuments require a detailed approach to the problem of scaffolding. Despite the short period of use we should pay particular attention to the possibility of anchoring scaffoldings. Performing static calculation allows minimizing the number of anchors and used elements.
Keywords: rusztowanie modułowe; prace na wysokości; schemat statyczny; modular scaffoldings; work at height; static scheme